Cohesive Devices in Zara Zetira's Novel - Rika Septiani (UNISAedu : Jurnal Ilmiah Ilmu Pendidikan, 2020)
This study w as focus on identifying the kind of cohesive devices, and describes the function of cohesive devices found in Zara Zetira Novel that entitle “Every Silent has Story”. Cohesive is the important element in paragraph to make the paragraph link together and be coherence also has a sense to make the reader interest, enjoy, and understanding every single paragraph on whole of the text. In analyzing process the writer used descriptive research method. The steps of the process this research are; reading, pick up the feature, specified the content, and looked for the percentage. As the result the writer found the higher frequency of cohesive devices and the result from the 1304 paragraph the data is divided again to the specific part. The result for the personal reference is 9349 or 89.0%, demonstrative 907 or 8.6%, comparative 244 or 2.3%. For nominal substitution are 98 or 42.2%, verbal 6 or 2.5%, and for the clausal substitution are 128 or 55.1%. The result of ellipsis is 18 in verbal ellipsis 10 or 55.5%, nominal ellipsis is 6 or 33.3% and causal ellipsis is 2 or 11.1%. For the additive conjunction is about 2158 or 64.2%, adversative 698 or 20.7%, clausal 286 or 8.5%, temporal 86 or 2.5%, and for the other conjunction the writer found 133 or 3.9%. In the lexical cohesion the writer found the data 946 or 99,8%. Lexical cohesion are divided into six part. For the repetition 545 or 57.6%, synonym 115 or 12.1%, hyponym 54 or 5.7%, metonym 18 or 1.9%, antonym 145 or 15.3%, and collocation 69 or 7.3%. Over all, from the data which found the higher frequency of the cohesive device in the novel is grammatical cohesion by the result 14111 or 99.15% whereas the lexical cohesion becomes a second rank by the result 946 or 99.9%. So, the author used grammatical and lexical cohesive in the novel, the cohesive mostly used is grammatical, and the dominant feature of cohesive is personal reference.